The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1029/2019gl082639
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of the 660‐km Discontinuity Beneath Southeastern China

Abstract: Imaging the structure of the 660‐km discontinuity is crucial to understanding the thermal and compositional states of the mantle transition zone. Here we study triplication data sampling beneath southeastern China and observe strong arrivals with rays turning at top of the lower mantle at an epicentral distance of 10°. Such strong arrivals indicate that the S velocity at the discontinuity increases by ~8.2±0.5% over less than 10 km. This sharp 660‐km discontinuity suggests that harzburgite enrichment exists at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 81 publications
(98 reference statements)
2
6
0
Order By: Relevance
“…The great similarity in waveforms between the data and the synthetics suggests that the preferred model replicated the observations well (Figure 8b). The sharp 660‐km discontinuity seen in this study is consistent with an early work by Castle and Creager (2000) and a recent work by Zhang M et al (2019), which suggest that the discontinuity is at most 10 km thick, and it is marginally consistent with a previous S‐to‐P conversion study that concluded the discontinuity is ≤5 km thick (Yamazaki and Hirahara, 1994). A sharp 660‐km discontinuity resulting from the post‐spinel transition was also revealed in a recent mineral physics experiment by Ishii et al (2019).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The great similarity in waveforms between the data and the synthetics suggests that the preferred model replicated the observations well (Figure 8b). The sharp 660‐km discontinuity seen in this study is consistent with an early work by Castle and Creager (2000) and a recent work by Zhang M et al (2019), which suggest that the discontinuity is at most 10 km thick, and it is marginally consistent with a previous S‐to‐P conversion study that concluded the discontinuity is ≤5 km thick (Yamazaki and Hirahara, 1994). A sharp 660‐km discontinuity resulting from the post‐spinel transition was also revealed in a recent mineral physics experiment by Ishii et al (2019).…”
Section: Resultssupporting
confidence: 92%
“…A subsequent study of the receiver function indicated that it is ~11.5 km thick (Lawrence and Shearer, 2006). A previous study of S‐to‐P converted waves (Castle and Creager, 2000) and a recent study on triplicated waves (Zhang M et al, 2019) both suggested that the 660‐km discontinuity is sharp (<10 km). However, other triplication studies have suggested the existence of a broad (~50 to 70 km thick) 660‐km discontinuity (e.g.,Wang BS and Niu FL, 2010; Li J et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, when the waveform period is greater than 3 s, it is impossible to distinguish the discontinuity between a sharp interface and a gradual one with 40 km thickness, even without adding noise. A similar frequency dependent feature has also been observed in previous triplication studies (Melbourne & Helmberger 1998;Zhang et al 2019).…”
Section: Frequency Dependent Resolution For Discontinuity Sharpnesssupporting
confidence: 86%
“…Receiver functions are a popular tool for investigating the 410 and 660 km discontinuities and the structure of the MTZ. Imaging the topographies of the 410 and 660 km discontinuities and the MTZ thickness plays a key role in understanding the thermal conditions of the MTZ (Agius et al., 2017; He et al., 2014; M. Zhang et al., 2019), thereby providing an indication of mantle convection within the Earth (Foulger, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the relationship between an upwelling mantle plume and the detailed topography of the upper mantle remains vague. Although a number of recent tomographic and receiver function studies have been carried out in NE China and nearby regions (e.g., Zhang et al, 2019;Fan et al, 2020;Kim et al, 2016;Zhu et al, 2019;Lu et al, 2020;Sun et al, 2020), the detailed structure of the mantle transition zone beneath NE China is still unclear.…”
Section: Accepted Articlementioning
confidence: 99%